Improvement of efficiency and flexibility in multi-slice helical CT - Sun, Wen-wu; Chen, Si-ping; Zhuang, Tian-ge (Shanghai jiao tong da xue xue bao, 2008)
One of the main aspects in computed tomography (CT) development is to make CT rapidly scan a large longitudinal volume with high z -axis resolution. The combination of helical scanning with multi-slice CT is a promising approach. Image reconstruction in multi-slice CT becomes, therefore, the major challenge. Known algorithms need to derive the complementary data or work only for certain range of pitches. A reconstruction algorithm was presented that works with the direct data as well as arbitrary pitches. Filter interpolation based on the proposed method was implemented easy. The results of computer simulations under kinds of conditions for four-slice CT were presented. The proposed method can obtain higher efficiency than the conventional method.